VDC_100102370126.0X000001. Issue 3 (March 2018) - Romanoff, Anya; Schmidt, Hank; Mcmurray, Matthew; Weltz, Christina; Schwartzman, Monica; Friedman, Kathryn; Margolies, Laurie; Port, Elisa
The role of MRI in the workup of newly diagnosed breast cancer patients remains controversial. Breast MRI detects additional disease, but this has not translated into improved outcomes. In light of a dramatic rise in MRI use, we investigated patterns of MRI ordering for newly diagnosed breast cancer. All newly diagnosed breast cancer cases presenting for surgical management to a specialized breast center from 2011 to 2013 were reviewed. Patients who had an MRI ordered by their operating surgeon were compared with those who had an MRI completed previously. Of 1037 patients, 504 (49%) with newly diagnosed breast cancer underwent MRI as part of their pre-operative evaluation. Variables associated with MRI use included commercial insurance, increased breast density, genetic testing, mamographically occult disease, and lobular pathology. Of women who presented to our center with an MRI already completed, 63 per cent were ordered by a primary care provider. Of the 504 patients, 233 (44%) who had an MRI underwent an additional biopsy, and 166 (33%) had a resultant change in management. There was no significant difference in MRI-directed change in patient care depending on ordering provider. Further research is needed to develop evidence-based guidelines for preoperative MRI evaluation to optimize patient outcomes.